Dual Roles of Protein as a Template and a Sulfur Provider: A General Approach to Metal Sulfides for Efficient Photothermal Therapy of Cancer. Issue 1 (17th November 2017) - Sheng, Jianping; Wang, Liqiang; Han, Yajing; Chen, Wansong; Liu, Hong; Zhang, Min; Deng, Liu; Liu, You‐Nian
Abstract: Fabrication of clinically translatable nanoparticles (NPs) as photothermal therapy (PTT) agents against cancer is becoming increasingly desirable, but still challenging, especially in facile and controllable synthesis of biocompatible NPs with high photothermal efficiency. A new strategy which uses protein as both a template and a sulfur provider is proposed for facile, cost‐effective, and large‐scale construction of biocompatible metal sulfide NPs with controlled structure and high photothermal efficiency. Upon mixing proteins and metal ions under alkaline conditions, the metal ions can be rapidly coordinated via a biuret‐reaction like process. In the presence of alkali, the inert disulfide bonds of S‐rich proteins can be activated to react with metal ions and generate metal sulfide NPs under gentle conditions. As a template, the protein can confine and regulate the nucleation and growth of the metal sulfide NPs within the protein formed cavities. Thus, the obtained metal sulfides such as Ag2 S, Bi2 S3, CdS, and CuS NPs are all with small size and coated with proteins, affording them biocompatible surfaces. As a model material, CuS NPs are evaluated as a PTT agent for cancer treatment. They exhibit high photothermal efficiency, high stability, water solubility, and good biocompatibility, making them an excellent PTT agent against tumors. This work paves a new avenue toward the synthesis of structure‐controlled and biocompatible metal sulfide NPs, which can find wide applications in biomedical fields. Abstract : Metal sulfide nanoparticles (NPs) with ultrasmall size, and good biocompatibility are facilely obtained via alkali‐driven transformation of S‐rich protein–metal complexes. Proteins work as both a sulfur resource and a template, where disulfide bonds are activated to react with metal ions and form metal sulfide NPs in situ, which are proved to be an excellent theranostic platform for cancer therapy.